A study on factors that contribute to customer satisfaction of Perkeso Kuala Pilah / Ras Nurdiana Abd Rashid - Abd Rashid, Ras Nurdiana (2014)
Customer satisfaction is considered to be one of the most important competitive factors for the future and one of the best indicators of a firm’s future profits. Perkeso Kuala Pilah is placed at the industrial area in Melang, Kuala Pilah Negeri Sembilan. The first manager of Perkeso Kuala Pilah is Mr Sabahnathan Rajah. Perkeso Kuala Pilah started their operation since 1st October 1974 until present. Perkeso Kuala Pilah became the main focus to determine the customer satisfaction. There are three independent variables that have been considered in measuring the customer satisfaction. The level of the customer satisfaction been determined based on the quality of facilities, services quality provided and also the environment of the building areas. This research is a study of customer satisfaction towards the quality of facilities, service quality and also the environment of the Perkeso Kuala Pilah. According to Juran (1981), customer satisfaction can be defined as the result achieved when the company meets or exceeds customer expectations over the lifetime of the product or services and when their product or services respond to customer needs. Jones and Sesser (1995), also indicates that providing customers with best value may be the only reliable way to achieve continuous customer satisfaction. The management must provide sufficient value to their customer in order to build strong satisfaction among the customers. Based on the research conducted before, there is a strong correlation between service quality and customer satisfaction, Sureshchandar et al (2002). It indicates that both service quality and customer satisfaction are independent and closely related. The purpose of this study is to determine either the customer is satisfied or not with the quality of facilities, service quality and environment provided for them. The results of this research also defined the strength and weaknesses of the Perkeso Kuala Pilah. Therefore, both customer and the management was gain beneficial through this research and this gives big impact for the customer satisfaction.